Dielectrophoresis has broad applicability to marker-free isolation of tumor cells from blood by microfluidic systems - Shim, Sangjo (American Institute of Physics, 2013)
The number of circulating tumor cells (CTCs) found in blood is known to be a prognostic marker for recurrence of primary tumors, however, most current methods for isolating CTCs rely on cell surface markers that are not universally expressed by CTCs. Dielectrophoresis (DEP) can discriminate and manipulate cancer cells in microfluidic systems and has been proposed as a molecular marker-independent approach for isolating CTCs from blood. To investigate the potential applicability of DEP to different cancer types, the dielectric and density properties of the NCI-60 panel of tumor cell types have been measured by dielectrophoretic field-flow fractionation (DEP-FFF) and compared with like properties of the subpopulations of normal peripheral blood cells. We show that all of the NCI-60 cell types, regardless of tissue of origin, exhibit dielectric properties that facilitate their isolation from blood by DEP. Cell types derived from solid tumors that grew in adherent cultures exhibited dielectric properties that were strikingly different from those of peripheral blood cell subpopulations while leukemia-derived lines that grew in non-adherent cultures exhibited dielectric properties that were closer to those of peripheral blood cell types. Our results suggest that DEP methods have wide applicability for the surface-marker independent isolation of viable CTCs from blood as well as for the concentration of leukemia cells from blood.